Rural development under the European CAP: The role of diversity - Marian Rizov (The Social Science Journal, 2005)
Achieving optimal diversity at community level is a key in solving the rural development problem. In this essay rural development at community level and the impact of Common Agricultural Policy (CAP) reforms are analyzed in the framework of privately provided public goods models. It is shown that CAP support redistribution inducing diversification of community activities across households can potentially have important positive impact on rural development and household welfare.
Keywords: Q18; Q12; R13; R11; 330; Rural development; Common Agricultural Policy; subsidies; welfare; diversity; comparative advantage